Fabric-Based Flexible Pressure Sensor Arrays with Ultra-Wide Pressure Range for Lower Limb Motion Capture System - Xiaohua Wu; Yuxuan Liang; Longsheng Lu; Shu Yang; Zhanbo Liang; Feilong Liu; Xiaoyu Lu; Bowen Xiao; Yilin Zhong; Yingxi Xie (Research)
The lower limb motion capture technology has garnered significant attention as a pivotal enabler in extended reality, sports science, film production, and medical rehabilitation. However, existing mature systems face critical challenges, including restricted operational environments, interference with natural activities, and cumbersome wearability. Here, a flexible insole pressure sensor array with an ultra-wide sensing range is developed using dip coating, laser cutting, and hot pressing, enabling lower limb motion capture. The developed fabric-based flexible pressure sensor exhibited an ultra-wide pressure range (3,770.9 kPa), high sensitivity (2.68 kPa−1), rapid response, recovery times (17.2 ms/3.5 ms), and high work life (>4 million loading/unloading cycles). The insole-shaped flexible pressure sensor array accurately measures pressure in different postures, achieving 95.5% classification accuracy across 10 dynamic and static poses. More importantly, the system achieved a joint position prediction accuracy of 7.8 pixels (~3.6 cm) in lower limb pose estimation. This high-precision lower limb motion capture system represents an ideal terminal for future extended reality applications, offering seamless integration, comfortable use, easily wearable design, and broad accessibility.